Randomized, blinded, placebo‐ and positive‐controlled crossover study to determine the effect of multiple doses of apixaban on the QTc interval. (14th January 2015) - Frost, Charles; Nepal, Sunil; Byon, Wonkyung; Moore, Kenneth; Reeves, Richard A.; Boyd, Rebecca; LaCreta, Frank
Abstract Apixaban is an oral, direct factor Xa inhibitor indicated for the prevention and treatment of thromboembolic disease. This randomized, blinded, 4‐way crossover study investigated the potential effect of apixaban on the QTc interval. Forty healthy subjects (39 completers) each received 3 days of the following treatments: blinded apixaban 10 mg once daily (QD), 50 mg QD (supratherapeutic), matched apixaban placebo QD, and a single dose of open‐label moxifloxacin 400 mg on Day 3, preceded by 2 days of placebo QD. Triplicate electrocardiograms obtained over 24 hours on Days −1 (baseline) and 3 were read by a blinded third party. The mean placebo‐adjusted, time‐matched, Fridericia‐corrected change from baseline QTc (ΔΔQTcF) for apixaban and moxifloxacin was estimated at each time point. The maximum ΔΔQTcF was 1.51 milliseconds (one‐sided upper 95% confidence interval [CI] 3.71 milliseconds) after apixaban 50 mg QD, 1.36 milliseconds (one‐sided upper 95%CI 3.54 milliseconds) after apixaban 10 mg QD, and 10.21 milliseconds (lower 95%CI 8.07 milliseconds) after moxifloxacin. Concentration‐response analysis suggested no evidence of a positive relationship between apixaban concentration and ΔQTcF. Apixaban doses up to 50 mg QD for 3 days were well tolerated and did not prolong the QTc interval in healthy subjects.